Pengaruh Bullying Terhadap Minat Siswa Smp N 3 Weleri Untuk Menjadi Atlet (Indonesian Journal for Physical Education and Sport, 2022)
Bullying is often considered a natural developmental process experienced by children and adolescents, so that it can affect the physical and psychological growth and development of both the perpetrator and the victim. The purpose of this study was to determine the general description, causal factors and effects of bullying on the interest of students of SMP N 3 Weleri to become athletes. This study uses a quantitative method with a descriptive research design. The population in this study were all students participating in extracurricular sports at SMP N 3 Weleri totaling 110 students. Data collection techniques used questionnaires, observation, documentation, and unstructured interviews. The data analysis technique used descriptive statistics. The results of this study indicate that many students do not understand the general picture of bullying. Family factors are the biggest trigger for bullying behavior. Bullying does not affect the interest of SMP N 3 Weleri students to become athletes. The conclusion of this study is the lack of socialization or debriefing about bullying from school and family, so that they have less insight. Family factors are a trigger for bullying behavior due to lack of attention from parents, especially for children from broken homes. Bullying is not a factor inhibiting the interest of SMP N 3 Weleri students to become athletes.